Pathogenic potential of human isolates of Aliarcobacter butzleri - Martins, Rodrigo Manuel Mendes (2021)
Since its discovery in 1991, the Aliarcobacter genus comprises 11 recognized species, including Aliarcobacter butzleri. This species has been described as a pathogen, being the fourth Campylobacter-related microorganism most commonly found in human diarrheic samples. Infections by this bacterium are often associated with abdominal cramps, nausea and watery diarrhoea. Although some studies described its pathogenic potential, still not much is known about its virulence mechanisms, which can complicate the treatment of infections caused by this microorganism and its control. In this manner, this work aimed to evaluate the different virulence phenotypic profiles of fifteen human isolates of A. butzleri. Initially, all isolates were typed by Multilocus Sequence Typing, which showed that all isolates belonged to different sequence types, pointing towards the genetic diversity of this bacterium. Next, several assays were performed to characterize the virulence phenotypic profile of each clinical isolate by assessing: (i) the antimicrobial profile through determination of the minimum inhibitory concentration (MIC) of six antibiotics of distinct classes; (ii) the susceptibility to reactive oxygen and nitrogen species; (iii) survival in acidic conditions (pH 4); (iv) the presence of the urease enzyme; (v) the resistance to bile salts; (vi) the chemotactic profile of each strain; (vii) the motility; (viii) differences in morphotype; (ix) biofilm formation ability; (x) haemolytic activity; (xi) survival in human serum; and (xii) the interaction between A. butzleri with the human colorectal adenocarcinoma cell line, Caco-2. Although, the clinical A. butzleri isolates under study, showed similar oxidative and nitrosative stress responses and morphotype, it was observed a great phenotypic variety among the isolates. Various isolates showed a multidrug resistance profile, with higher resistance frequency being observed for the antibiotics: ertapenem (100%), tetracycline (93.3%), and ampicillin (86.6%). Considering the potential survival of the isolates through the gastrointestinal system, the isolates demonstrated diverse resistance profiles against acidic conditions, with six strains having a positive phenotype for the presence of the urease enzyme, but all demonstrated to be resistant do the bile salts concentrations found in the human gut. Distinct chemotactic profiles indicating a possible interaction with compound of the human mucosa were observed. The isolates under study demonstrated low motility or a diverse profile of higher motility, and different profiles of biofilm formation classified from weak to strong biofilm formers. The A. butzleri isolates showed weak haemolytic activity and low survival in the human serum, with exception of one. Only seven strains demonstrated to be capable of invading Caco-2 cells, while all showed to be adherent to the cell line despite at different levels. The effect of aerobic conditions in the phenotype has also been studied on three isolates presenting distinct phenotypic profiles (INSA Cu 29393, INSA 3202 e INSA 3711). To evaluate the differences in the phenotypic profile when subjected to different atmospheric conditions (aerobiosis and microaerophilia), a similar characterization to the one done for assessment of the phenotypic profile of the clinical isolates was performed. Overall, the aerobic conditions seemed to have a positive effect in the haemolytic activity and motility of the isolates, although having no impact on the flagellin A expression. Further, the aerobic conditions also negatively affected the oxidative stress resistance of the isolates, with the remaining assays showing a strainspecific response. In conclusion, taking into account the results obtained, we can acknowledge that a great phenotypic variability can be found among the clinical isolates of A. butzleri studied, which may be associated with a different host-bacterium interaction.